Understanding Radiographic Measurements Used in Foot and Ankle Surgery. Issue 2 (15th January 2022) - Lau, Brian C.; Allahabadi, Sachin; Palanca, Ariel; Oji, David E.
Abstract : Given the high volume of patient visits for foot and ankle complaints, developing a systematic approach to evaluation of foot and ankle pathology is important for orthopaedic providers. A thorough evaluation of weight-bearing radiographs is essential to differentiate acute and chronic injury from normal findings to dictate treatment. Radiographic changes and varying degrees of deformity can influence surgical considerations. The purpose of this article was to review and define radiographic measurements relevant to surgical decision making for common foot and ankle pathologies and treatment.